Current results of left ventricular assist device therapy in France: the ASSIST-ICD registry. (16th April 2020) - Anselmi, Amedeo; Galand, Vincent; Vincentelli, André; Boule, Stéphane; Dambrin, Camille; Delmas, Clément; Barandon, Laurent; Pernot, Mathieu; Kindo, Michel; Tam, Hoang Minh; Gaudard, Philippe; Rouviere, Philippe; et al.
Abstract: OBJECTIVES: Our goal was to provide a picture of left ventricular assist device (LVAD) activity in France between 2007 and 2016 based on the multicentric ASSIST-ICD registry. METHODS: We retrospectively collected 136 variables including in-hospital data, follow-up survival rates and adverse events from 671 LVAD recipients at 20 out of 24 LVAD implant centres in France. The average follow-up time was 1.2 years (standard deviation: 1.4); the total follow-up time was 807.5 patient-years. RESULTS: The included devices were the HeartMate II ®, HeartWare LVAS ® or Jarvik 2000 ® . The overall likelihood of being alive while on LVAD support or having a transplant (primary end point) at 1, 2, 3 and 5 years postimplantation was 65.2%, 59.7%, 55.9% and 47.7%, respectively, given a cumulative incidence of 29.2% of receiving a transplant at year 5. At implantation, 21.5% of patients were on extracorporeal life support. The overall rate of cardiogenic shock at implantation was 53%. The major complications were driveline infection (26.1%), pump pocket or cannula infection (12.6%), LVAD thrombosis (12.2%), ischaemic (12.8%) or haemorrhagic stroke (5.4%; all strokes 18.2%), non-cerebral haemorrhage (9.1%) and LVAD exchange (5.2%). The primary end point (survival) was stratified by age at surgery and by the type of device used, with inference from baseline profiles. The primary end point combined with an absence of complications (secondary end point) was also stratified by device type. CONCLUSIONS: The ASSIST-ICD registry provides a real-life picture of LVAD use in 20 of the 24 implant centres in France. Despite older average age and a higher proportion of patients chosen for destination therapy, survival rates improved compared to those in previous national registry results. This LVAD registry contrasts with other international registries because patients with implants have more severe disease, and the national policy for graft attribution is distinct. We recommend referring patients for LVAD earlier and suggest a discussion of the optimal timing of a transplant for bridged patients (more dismal results after the second year of support?).